PENGARUH RESILIENSI TERHADAP KINERJA KARYAWAN DENGAN JOB INSECURITY SEBAGAI MEDIATOR - Arnelita Natalie Antonio; Jimmy Ellya Kurniawan (ITB AAS Indonesia Surakarta, 2024)
The COVID-19 pandemic has left a tremendous impact on the global economy, particularly in terms of reducing the number of employees. This phenomenon can affect the job insecurity of employees who have not experienced layoffs. This study aims to determine the influence of resilience on employee performance and the influence of job insecurity as a mediating variable between resilience and employee performance. This research uses a quantitative method with a correlational design. The respondents in this study are 106 employees currently working in companies that have laid off more than 10 people in the last year. The results of the mediation test on the resilience variable towards employee performance directly indicate a significant positive influence (p-value